Challenges and perspectives of attracting talents from developing countries - the case study of Horizon Education Agency in Azerbaijan - Mammadli, A.; Barakos, George; Dorward, K.W.; Malikzada, N.; Hasanzade, H.; Mehraliyeva, S. (AusIMM, 2024)
Azerbaijan has a mature petroleum industry, but the country’s mineral resources sector is still developing. The lack of a robust domestic mining industry has resulted to a shortage of professionals in academia and industry able to mentor young talents, and to outdated and insufficient education which has led a few Azerbaijani geology and mining students to seek further training and job opportunities abroad. Recognising this gap, a group of postgraduate and undergraduate university students based primarily in Baku and other locations worldwide, using their experiences and knowledge from studying abroad, decided to put their skills to use in a new context. Hence, these students established the Horizon Education Agency (HEA), the main goal of which has been to give their Azerbaijani peers relatively straightforward access opportunities to educational programs in foreign institutions, scholarships’ awareness, and participation in regional and global initiatives. Since 2018, this small group of Azerbaijani students has organised several seminars, online workshops, and internship programs, in addition to launching a series of conferences called the ‘Global Engineering Symposium’ (GES). HEA invited academics and industry experts from around the world to Baku, attracting the interest of hundreds of university students. Through participation at GES, students were able to increase their knowledge and skills, and be motivated to seek engineering careers’ paths in Azerbaijan and abroad. Many conference participants afterwards sought opportunities abroad for their postgraduate studies. In recent years, students have been studying at universities in China, Europe, and the United States. After finishing their studies abroad, some decided to return to Azerbaijan with the invaluable information and skills they gained from their international experiences. This inflow of highly educated individuals has the potential to substantially improve Azerbaijan’s mining sector and academic scene, encouraging innovation and promoting advancement in many fields.